2019
DOI: 10.1007/s10142-019-00680-5
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome deletion in p53 mutant mice enhances apoptotic and anti-tumorigenic responses to UV damage at the transcriptome level

Abstract: Previous studies have demonstrated that deletion of Cryptochrome (Cry) genes protects p53-/mutant mice from early onset of cancer and extends their median lifespan by about 1.5 fold. Subsequent in vitro studies had revealed that deletion of Crys enhances apoptosis in response to UV damage through activation of p73, and inactivation of GSK3β. However, it was not known at the transcriptome-wide level how deletion of Crys delays the onset of cancer in p53-/mutant mice. In this study, RNA-seq approach was taken to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Several attempts have been made to correlate clock gene polymorphisms or expression levels in either cancer cell lines or tissues from various cancers to determine whether clock gene mutations ( 62 ) or levels of expression ( 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ) play a role in initiation or progression of cancer and susceptibility of cancer to a particular drug and a particular time of day for delivery of the drug (chronochemotherapy). The effects of clock gene polymorphism are small, and both predisposing and protective mutations were observed in comparable levels, and thus it is unclear whether these associations have a pathogenic role in the observed phenotypes ( 33 ).…”
Section: Circadian Clock–carcinogenesismentioning
confidence: 99%
“…Several attempts have been made to correlate clock gene polymorphisms or expression levels in either cancer cell lines or tissues from various cancers to determine whether clock gene mutations ( 62 ) or levels of expression ( 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ) play a role in initiation or progression of cancer and susceptibility of cancer to a particular drug and a particular time of day for delivery of the drug (chronochemotherapy). The effects of clock gene polymorphism are small, and both predisposing and protective mutations were observed in comparable levels, and thus it is unclear whether these associations have a pathogenic role in the observed phenotypes ( 33 ).…”
Section: Circadian Clock–carcinogenesismentioning
confidence: 99%
“…And this study preliminarily investigated that miR-29a affects the invasion and migration of residual A549 cells after radiation by regulating the interaction between PER1 and LAMR1. The Per1 gene is located at 17p13.1p12 and encodes a protein about 1290 amino acids long with a molecular mass of 136 kD, whose protein is mainly localized in the nucleus.Per1 is an oncogene that regulates many key cell cycle proteins downstream, leading to alterations in cell cycle and proliferation that are closely associated with cancer development [15]. In another study on glioma, it was found that down-regulation of Per1 gene expression reduced the sensitivity of U343 glioma cells to X-ray irradiation and decreased glioma cell apoptosis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as previously shown, deletion of Cry genes in p53 -/in C57BL/6J background enhances the lifespan of the animals by protecting animals from cancer death 35 . A recent transcriptomic study revealed that differential regulation of nuclear factor kappa B (NF-κB) regulation may increase survival rate 36 . We wished to test M47 on p53 -/animals to see whether it delays cancer death and change the lifespan in cancer prone p53 -/in C57BL/6J mice.…”
Section: Effect Of M47 On the Lifespan Of P53 -/Micementioning
confidence: 99%